BORROWED POLISH WORDS IN «MATERIALS TO THE DICTIONARY OF WRITTEN AND LITERARY UKRAINIAN LANGUAGE OF THE XV-XVIII CENTURIES» BY YEVHEN TYMCHENKO - Yevdokimova, O. (Linguistic and Conceptual Worldviews, 2020)
The article, which is based on the first historical scientifically compiled dictionary of the Ukrainian language «Materials to the dictionary of written and literary Ukrainian language of the XV-XVIII centuries» by Yevhen Tymchenko, provides a brief overview of the lexical composition with the identification of the XVI-XVII centuries Old Ukrainian language words borrowed from the Polish language. For this purpose, lexical-thematic groups (human existence, spiritual life, the realities of the environment etc.) and lexical-semantic groups (educational, world of flora and fauna, nomenclature of clothing, footwear, jewelry and fabrics, architecture, customs etc.) of borrowed Polish words have been distinguished and the quantitative composition of each group have been evaluated. The contexts in which the specified vocabulary functions have been provided. The fact that noted borrowed Polish words do not dominate in all lexical-thematic groups, though they are a constituent of each, has been revealed. The examples of contexts of the texts that serve as a source of reference for the study and fixation of borrowing by linguistic researchers, including Polonisms, in the Ukrainian language are given. Synonymous and antonymous groups, derivational nests, constant expressions and phraseologisms, in which the given borrowed Polish words occur, have been provided. It is defined, that multi-valued Polonisms can function within the same lexical-semantic group or belong to different groups. The list of researchers who dealt with the study of borrowed Polish words in the Ukrainian language has been given. Considering historical contacts, both social and cultural affinity and geographical neighborhood of Ukrainian and Polish peoples, the time period of intensive entry of borrowed Polish words into the Ukrainian language has been determined.